Mental health of women who have had an abortion (Research, Society and Development, 2022)
Spontaneous abortion occurs before the 20th gestational week and has a multifactorial origin, the unexpected interruption of your pregnancy, where the child is anxiously awaited, can modify the functioning of the woman's body. Thus, the present work aims to analyze the changes that occur in the mental health of women who suffer abortion between the consequences of emotional and psychological damage. This study is based on a narrative and descriptive literature review, with a qualitative and quantitative approach. Abortion is understood as a serious public health problem, it involves religious, cultural, economic aspects, between January and June 2022 there were a total of 34,992 cases of spontaneous abortions in Brazil. Legalized induced abortion is performed through hospital services and judicial authorization, within these units adequate assistance to women, taking the risks to their health. from January to June 2022 there were a total of 1,004 records of abortions performed for medical reasons. On the other hand, illegal induced abortion requires a certain awareness of: methods used by the woman herself, untrained professionals, with some risks such as death. Thus, it is essential that health professionals are aware of the needs of these women, both when they undergo an abortion and in the period after the fact.